Combined repetitive facilitative exercise under continuous neuromuscular electrical stimulation and task-oriented training for hemiplegic upper extremity during convalescent phase after stroke: before-and-after feasibility trial - Fujimoto, Koya; Ueno, Makoto; Etoh, Seiji; Shimodozono, Megumi (Frontiers in Neurology, 2024)
Introduction Whereas repetitive facilitative exercise (RFE) affects primarily recovery of motor impairment after stroke, task-oriented training (TOT) focuses on facilitating daily use of the affected upper extremity. However, feasibility of combined RFE and TOT has not been reported. We originated “task-oriented RFE,” as a new combination therapy for patients with hemiplegic upper extremity after subacute stroke, to examine its feasibility in convalescent rehabilitation wards. Methods This is a before-and-after pilot study. Eight patients with hemiplegic upper extremity after subacute stroke received the task-oriented RFE program for 6 weeks at 80 min per day (20–60 min of TOT applied after 60–20 min of RFE under continuous neuromuscular electrical stimulation) in a convalescent rehabilitation ward. In the current program, we introduced the Aid for Decision-making in Occupation Choice (ADOC) iPad application as a goal-setting method for determining tasks. Feasibility was assessed with adherence to the protocol, adverse events in response to the intervention, and preliminary efficacy. Motor functions, amount of use and quality of movement in the hemiparetic upper extremity, and satisfaction of the patients were evaluated with Fugl-Meyer Assessment (FMA), the Action Research Arm Test (ARAT), the motor activity log (MAL) for the amount of use (AOU) and quality of movement (QOM) of the paralyzed hand, and ADOC. Results All participants accomplished the program, which was implemented as originally planned; neither nonattendance nor an adverse event occurred during the study. Favorable outcomes were obtained with all measures; mean changes in FMA, ARAT in the dominant hand, MAL-AOU, and MAL-QOM were greater than minimal clinically important differences. Mean changes in ADOC were greater than the minimal detectable change. Discussion The task-oriented RFE program was safe, well-tolerated, beneficial, and feasible within 80 min a day of occupational therapy, which means also within the procedural constraints of the Japanese health insurance system during the convalescent phase. Future studies are warranted to examine whether combined RFE and TOT enhances the efficacies of each program alone.